THE ROLE OF SOCIAL CAPITAL IN FOSTERING CHARACTER EDUCATION IN PRIMARY SCHOOLS: KI HADJAR DEWANTARA’S PERSPECTIVES - Zulfiati, Heri Maria; Praheto, Biya Ebi; Sudirman, Anselmus (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2021)
To foster character education in Indonesia, research on the role of social capital has become an urgent issue because character crisis is one of the growing concerns and recent stunning news stakes. National identity crises have shown anti-cultural behavior, anti-character, and less use of domestic social capital blatantly. This research aims to describe the role of social capital that determines the implementation of character education through Ki Hadjar Dewantara’s perspectives. This qualitative research was designed as a case study using purposive sampling with individual resources such as headmaster, teacher, student representatives, school committee, parents, foundation management, and school supervisor. This research was conducted at Tamansiswa Primary School, Yogyakarta, Indonesia, from November 2017 to January 2018. The research result shows that the social capital role determines the implementation of character education, and in Ki Hadjar Dewantara’s perspective, character education has been applied in all learning processes. Both intra-curricular and extracurricular activities support the school culture, and the family system is an integral part of habituation and exemplary character inculcation at school, family, and societal levels through mutual love, respect, assistance, and help. The obliged elements of social capital in embodying character education are trust, norm, and network.